PENGARUH TINGKAT PENDIDIKAN DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI PADA BALAI LATIHAN KERJA (BLK) METRO - Neysa Amallia (e-JKPP, 2018)
ABSTRACT  Development of human resources quality in the organization has an important role, the success of an organization is determined by effective human resource management. The research method used in this research is survey method with quantitative approach. The populations of this study are all employees, there are 34 employees of BalaiLatihanKerja(BLK) Metro.The researchresultshows that there is a significant influence between education level variable towards employee performance at Balai Pelatihan Kerja (BLK) Metro with P (Sig) = 0,000 ≤ α = 0,05. There is significant influence between work facilities variable towards employee performance at Balai Pelatihan Kerja (BLK) Metro with P (Sig) = 0,000 ≤ α = 0,05. Simultaneously there is significant influence between educationlevel and work facilities towards employee performanceat Balai Pelatihan Kerja( (BLK) Metro. The result of simultaneous hypothesis test between educationlevel and work facilities towards employee performance at Balai Pelatihan Kerja (BLK) Metro with P (Sig) = 0,000 ≤ α = 0,05. The result of Multiple linear regression between education level and work facilities towards employee performance at Balai Pelatihan Kerja (BLK) Metro obtained Y = 9,955 + 0,583 X1 + 0,403X2.